E Safaah Sistem Informasi Pejabat Pengelola Informasi Dan Dokumentasi (PPID) Dinas Komunikasi Informatika Sandi Dan Statistik (Diskomsantik) Berbasis Android - Kurniawan, Dzikry; Eva Safaah; Jubaedi, Ahmad Dedi (Universitas Serang Raya, 2023)
Abstract Information and Documentation Management Officer (PPID), functions as a manager and conveyer of documents owned by public bodies in accordance with the mandate of Law 14/2008 concerning Public Information Disclosure. The development of information and communication technology in this era of globalization is growing rapidly. With the high need for information, the faster the information system will develop, especially in the use of information. As in the Tangerang PPID information system, Jakarta PPID, Subang PPID, and Semarang PPID which have been developed into an Android-based information system. The method used in the development of this final project information system is the Waterfall Method. The research was conducted at the Department of Communication, Informatics, Passwords and Statistics (DISKOMSANTIK) of Pandeglang City. Data collection and data analysis techniques were system engineering, requirement analysis, design, coding, testing, and maintenance. The results obtained are that the writer can develop an information system for Android Information Management Officers, Information system development, Android Information Management and Documentation Officers (PPID). Keywords: Android, Development, information system, Information Management and Documentation Officer (PPID), pandeglang.